2022
DOI: 10.1186/s12935-022-02534-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel sequential therapy with metformin enhances the effects of cisplatin in testicular germ cell tumours via YAP1 signalling

Abstract: Background Testicular germ cell tumours (TGCTs) are the most commonly diagnosed malignancy in young men. Although cisplatin has been shown to be effective to treat TGCT patients, long-term follow-up has shown that TGCT survivors who accepted cisplatin treatment suffered from a greater number of adverse reactions than patients who underwent orchiectomy alone. As metformin has shown an anticancer effect in various cancers, we investigated whether metformin could enhance the effects of cisplatin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The IGFs system has an essential role in the normal development and embryonic migration of PGCs, as well as in the tumorigenic process of these cells, including cisplatin-resistance and metastatic spread of male GCTs, often characterized by sustained activity of the IGF1R signaling pathway ( 55 ). In this context, the potential of Met as an effective adjuvant therapy reverting cisplatin-resistance in male GCTs, has recently been reported ( 56 ). In particular, in the human TCam-2 cell line (a model of cisplatin resistant primary tumor of the testis), the antiproliferative and antimigratory activities of Met have been shown to intersect with the Hippo pathway ( 56 ), a newly discovered tumor suppressor cascade downstream of HMGA1, which is deregulated in several human cancers, including the malignant tumors of the breast ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IGFs system has an essential role in the normal development and embryonic migration of PGCs, as well as in the tumorigenic process of these cells, including cisplatin-resistance and metastatic spread of male GCTs, often characterized by sustained activity of the IGF1R signaling pathway ( 55 ). In this context, the potential of Met as an effective adjuvant therapy reverting cisplatin-resistance in male GCTs, has recently been reported ( 56 ). In particular, in the human TCam-2 cell line (a model of cisplatin resistant primary tumor of the testis), the antiproliferative and antimigratory activities of Met have been shown to intersect with the Hippo pathway ( 56 ), a newly discovered tumor suppressor cascade downstream of HMGA1, which is deregulated in several human cancers, including the malignant tumors of the breast ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the potential of Met as an effective adjuvant therapy reverting cisplatin-resistance in male GCTs, has recently been reported ( 56 ). In particular, in the human TCam-2 cell line (a model of cisplatin resistant primary tumor of the testis), the antiproliferative and antimigratory activities of Met have been shown to intersect with the Hippo pathway ( 56 ), a newly discovered tumor suppressor cascade downstream of HMGA1, which is deregulated in several human cancers, including the malignant tumors of the breast ( 57 ). Herein, for the first time, we provide evidence that Met inhibits the proliferation, migration and in vitro spherogenic growth of SEM-1 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that different immune status in TME may be responsible for the different survival outcomes of TGCT patients ( 103 ). Moreover, YAP1 inhibition enhanced the chemosensitivity of cisplatin in TGCT ( 104 ). Studies about the YAP1 in immunomodulation in TGCT remain absent.…”
Section: Discussionmentioning
confidence: 99%
“…G1 phase arrest was observed in TCam-2 and NTERA-2 when metformin was withdrawn for 24 h. Combination treatment with metformin and cisplatin enhanced the anticancer effects, showing a potent reduction of cell proliferation as evidenced by decreased nuclear abundance of cyclin D1. Metformin also de-creased the expression of IGFBP1, IGF1R, and MMP-11, which led to a decrease in HMGA1 abundance [169,170].…”
Section: Other Targeted Therapies (Otts)mentioning
confidence: 99%